The LRXs-RALFs-FER module controls plant growth and salt stress responses by modulating multiple plant hormones - Zhao, Chunzhao (Natl Sci Rev, 2020)
Salt stress is a major environmental factor limiting plant growth and productivity. We recently discovered an important new salt tolerance pathway, where the cell wall leucine-rich repeat extensins LRX3/4/5, the RAPID ALKALINIZATION FACTOR (RALF) peptides RALF22/23 and receptor-like kinase FERONIA (FER) function as a module to simultaneously regulate plant growth and salt stress tolerance. However, the intracellular signaling pathways that are regulated by the extracellular LRX3/4/5-RALF22/23-FER module to coordinate growth, cell wall integrity and salt stress responses are still unknown. Here, we report that the LRX3/4/5-RALF22/23-FER module negatively regulates the levels of jasmonic acid (JA), salicylic acid (SA) and abscisic acid (ABA). Blocking JA pathway rescues the dwarf phenotype of the lrx345 and fer-4 mutants, while disruption of ABA biosynthesis suppresses the salt-hypersensitivity of these mutants. Many salt stress-responsive genes display abnormal expression patterns in the lrx345 and fer-4 mutants, as well as in the wild type plants treated with epigallocatechin gallate (EGCG), an inhibitor of pectin methylesterases, suggesting cell wall integrity as a critical factor that determines the expression pattern of stress-responsive genes. Production of reactive oxygen species (ROS) is constitutively increased in the lrx345 and fer-4 mutants, and inhibition of ROS accumulation suppresses the salt-hypersensitivity of these mutants. Together, our work provides strong evidence that the LRX3/4/5-RALF22/23-FER module controls plant growth and salt stress responses by regulating hormonal homeostasis and ROS accumulation.